The Implementation of Project Based Learning to Improve Students’ Numeracy at SDN 028227 Binjai Selatan - Panjaitan, Efrini; Pradwita, Friska Amanda; Br Sitompul , Keren Hapukh R.M; Rambe, Tiurlina; Sitepu, Dwi Hany Fatmawati (LINGUISTIK TERAPAN, 2024)
This study investigates the effectiveness of Project Based Learning (PjBL) in enhancing numeracy skills among students at SDN 028227 Binjai Selatan Strucktre. The research employs a Classroom Action Research (CAR) design, which includes planning, implementing, observing, and reflecting through three distinct cycles. Each cycle involved a series of projects designed to engage students actively in their learning process. Results indicate a significant improvement in students' numeracy skills, with completion rates rising from 40% in the first cycle to an impressive 79% in the third cycle. The qualitative data collected through observations and student feedback further support these findings, highlighting increased student engagement and motivation towards mathematics. Additionally, students reported a greater understanding of mathematical concepts as they applied their knowledge to real-world problems through project work. This demonstrates that PjBL can effectively foster a deeper understanding of mathematical concepts and improve overall learning outcomes. The study concludes that implementing PjBL not only enhances numeracy skills but also promotes critical thinking and collaboration among students, making it a valuable pedagogical approach for educators aiming to improve mathematics education in elementary schools.